Reaching to heaven : a spiritual journey through life and death - Van Praagh, James (New York Dutton, 1999)
Tells how to develop one's spiritual core, and relates the stories of individuals who have found comfort in communications from their deceased loved ones
Quality Paperback, 11/99
Keywords: Spiritualism